TRIM31 triggers colorectal carcinogenesis and progression by maintaining YBX1 protein stability through ubiquitination modification - Xiaoqing Li; Ying Wu; Jiahao Guo; Peng Huang; Qiuhui Li; Zhongyu Gao; Yanming Hu; Aidi Gao; Ming Sun; Han Min; Jundong Zhou (Cell Death and Disease)
Abstract Colorectal cancer (CRC) is one of the most common gastrointestinal tumors, and one of the leading causes of cancer-related deaths worldwide. However, the molecular mechanisms underlying CRC development and progression have not been fully elucidated until now. Emerging studies have shown that post-translational modifications of proteins, especially ubiquitination modifications, play an important role in tumorigenesis and progression. Here we identified that the E3 ligase TRIM31, a member of the TRIM (Tripartite Motif) family proteins, is highly expressed during colorectal inflammation-cancer transformation and is associated with poor prognosis in CRC patients. Knockdown of TRIM31 expression led to the suppression of CRC cell proliferation and migration in vitro, tumor formation and metastatic ability in vivo. TRIM31 interacts with YBX1 and catalyses the Lys63 (K63) linkage polyubiquitination of Lys81 on YBX1, which ultimately leads to the stabilization of the YBX1 protein. YBX1 further enhances the stabilization of mRNAs for EREG, GAS6, and MAFG through both m5C site-dependent and -independent recognition routes. In addition, activation of NF-κB promotes the binding of P65 to the promoter region of TRIM31 to activate the transcription of the TRIM31 gene. Furthermore, TRIM31 facilitates the entry of P65 into the nucleus, which in turn creates a positive feedback pathway that promotes inflammatory-carcinogenic transformation and tumorigenesis of colorectal. Our findings indicate that TRIM31 may be an important factor driving colorectal carcinogenesis, providing a potential target for intervention in CRC targeted therapy.